Topics in Heart Failure Management 2019
DOI: 10.5772/intechopen.82416
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure in Sub-Saharan Africa

Abstract: Sub-Saharan Africa (SSA) is currently experiencing multiple burden of disease as a result of demographic and epidemiologic transition. This is occasioned rapid urbanization, unhealthy diets rich in fats and salt, western lifestyle and sedentary living. Heart failure (HF) has become a global public health issue. It is associated with high morbidity and mortality, frequent hospitalization and high economic cost. In SSA, HF is a disease of young and middle-aged adults with the attendant high disability-adjusted l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 151 publications
0
15
1
2
Order By: Relevance
“… 7 Both findings were similar to data from SSA, which revealed that HF is a disease of young and middle age. 17 Nonetheless, the mean age is about 8 years younger than patients in studies reported from developed countries. 18 This might be due to the younger population structure in Sudan.…”
Section: Discussionmentioning
confidence: 85%
“… 7 Both findings were similar to data from SSA, which revealed that HF is a disease of young and middle age. 17 Nonetheless, the mean age is about 8 years younger than patients in studies reported from developed countries. 18 This might be due to the younger population structure in Sudan.…”
Section: Discussionmentioning
confidence: 85%
“…The prevalence of congestive heart failure was 0.3%. Heart failure in Sub-Saharan Africa represents approximately 9.4-42.5% of all medical admissions and 25.6-30.0% of admissions into cardiology units (Agbor et al, 2018;S. Ogah et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The burden of cardiovascular disease in sub-Saharan Africa (SSA) has increased as it proceeds through the epidemiological shift from infectious diseases to chronic non-communicable diseases [1]. Heart failure (HF) is a terminal complication of many cardiovascular diseases, and is responsible for a growing number of hospitalizations in SSA [2][3][4][5][6]. With the rapid increase in the prevalence of HF risk factors in SSA, the burden of HF is expected to grow in future years [1,7].…”
Section: Introductionmentioning
confidence: 99%